NEW METHODS FOR ACTIVATION OF ASPHALT MINERAL FILLERS ASPHALT PLANT - Ya. N. Kovalev; S. S. Budnichenko (Наука и техника)
The paper considers the possibility of activation methods for asphalt mineral fillers while using the present process equipment at the asphalt plant.